"When sense of time disappears"—Or does it? Online video gamers' time management and time apprehension. (July 2016) - Majamäki, Maija; Hellman, Matilda
Massively multiplayer online role-playing games are graphical virtual environments in which gamers interact with each other through avatars many hours a day on a daily basis. The most widely accepted criterion of problematic variants of the gaming is the amount of time spent on the games. In this study, we show that time use might not be a very adequate measurement of the extent of the problem. We have analyzed an interview material with 17 (=n) gamers, and 115 (=n) applications to a gamers' guild, identifying gamers' perception of time and temporality. Firstly, our study shows that time spent on gaming varies a lot over time depending on other life activities and the overall life situation of the gamer. Secondly, our study indicates that due to the nature of the activity, gamers can develop time management skills over time. Concrete techniques to enjoy the flow of the game, but still function well in other life spheres involve, for example, economizing other activities, setting alarm clocks, and schedule "gaming binges." We also discuss some conceptual differences made between serious leisure, on the one hand, and addiction, on the other.